Sobre la “presencia” del objeto de conocimiento en la teoría de la intencionalidad de Duns Escoto - Vargas, Julio C. (2020)
“On the ‘presence’ of the Object of Knowledge in Duns Scotus’ Theory of Intentionality”. This paper deals with Duns Scotus’s intentional Theory and poses the question on the presence of the intentional object, its modalities and how the identification is made, as a first level of knowledge. Throughout this paper, two forms of the presence are explained: on the one hand, through the sensible species and the image and, on the other hand, through the intelligible species. The aim is to determine up to which point the intelligible species can help to enhance the brilliance of the intentional object with the support of the a priori forms, the universals. The correspondence between the intentional object and the common nature leads to posing the question for the unity of the essence or common nature, in so far as the essence precedes the realisation of the intentional act. Keywords